Evidence that hepatitis B virus replication in mouse cells is limited by the lack of a host cell dependency factor - Lempp, Florian A.; Mutz, Pascal; Lipps, Christoph; Wirth, Dagmar; Bartenschlager, Ralf; Urban, Stephan (Journal of hepatology, 2016)
Hepatitis B virus (HBV) is a major human pathogen restricted to hepatocytes. Expression of the specific receptor human sodium taurocholate cotransporting polypeptide (hNTCP) in mouse hepatocytes renders them susceptible to hepatitis delta virus (HDV), a satellite of HBV; however, HBV remains restricted at an early stage of replication. This study aims at clarifying whether this restriction is caused by the lack of a dependency factor or the activity of a restriction factor.
Available online 11 November 2015
Gesehen am 17.06.2020